2010
DOI: 10.1021/je100671v
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Properties, Viscosities, and Isobaric Heat Capacities of Imidazolium Octanoate Protic Ionic Liquid in Molecular Solvents

Abstract: Densities (F), viscosities (η), and isobaric heat molar capacities (C p ) of binary mixtures containing imidazolium octanoate, [Im][C 7 CO 2 ], a protic ionic liquid (PIL), with four molecular solvents, water, acetonitrile, ethanol, and 1-octanol, are determined as a function of temperature from (298.15 to 323.15) K and within the whole composition range at atmospheric pressure. Excess molar volumes, V E , excess molar heat capacities, C p E , and the deviation from additivity rules of viscosities, ∆η, of imid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 43 publications
8
35
0
Order By: Relevance
“…The [38] [38] a Standard uncertainties, u, are: u(T) = 0.01 K, u(p) = 0.002 MPa, the relative standard uncertainty, u r , is u r (η) = 5%.…”
Section: Discussionmentioning
confidence: 99%
“…The [38] [38] a Standard uncertainties, u, are: u(T) = 0.01 K, u(p) = 0.002 MPa, the relative standard uncertainty, u r , is u r (η) = 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Densities of water [17] and ethanol [14] for applying equation (1) heat capacities, being higher than those of Zábranský et al [18] and Anouti et al [20] and lower than those of García-Miaja et al [19] and Vega-Maza et al [22]. The deviations from the values calculated through the polynomial of Zábranský et al [18], which are likely the best ones, range from 0.2% at the higher temperature to 0.4% at the lower one.…”
Section: Equipmentmentioning
confidence: 99%
“…From this comparison, it can be concluded that the equipment has a good performance. [18] () García-Miaja et al [19]; (▼) Anouti et al [20]; () Tripathi [21]; () Vega-Maza et al …”
Section: Equipmentmentioning
confidence: 99%
“…1 In relation to industrial applications of these new compounds, a big effort is currently done to gather and describe experimental thermodynamics data of either pure ionic liquids or of mixtures thereof with aqueous or non-aqueous solutions. [2][3][4][5][6] Few data for osmotic or activity coefficients of aqueous ionic liquids solutions have been reported [7][8][9][10][11][12][13][14][15] and most thermodynamics electrolyte models such as Pitzer, NRTL or e-NRTL models, or more recently COSMO-SAC 16 , have been used to describe these thermodynamic quantities. Even though models were found to describe successfully the binary systems composed of an ionic liquid and a solvent, the parameters within these models are semi-empirical, yielding potential extrapolations to the description of mixtures difficult -if not impossible -and rather unreliable.…”
Section: Introductionmentioning
confidence: 99%